Time of Transmission of the loss in international sales Study accordance of Iraqi law& un convention on contracts for the international sale of goods (Vienna 1980) - جودة عبد الله عبد السادة; امين خالص نافع (Journal of Legal Sciences, 2021)
This study deals with the topic time of transmission of loose international sales، which is defined by the Vienna Convention on the International Sale of Goods as "passing of risk" As a basis for "the transfer of liability from the seller’s custody to the buyer’s guarantee. This expression was adopted by the legislator from the Islamic jurisprudence, which is in an acceptance interview in the real estate legislation. The arrest does not require that the actual possession of the goods has actually been done by the buyer. On the face of the buyer can be caught without a hail, and the Iraqi Trade Law No. 30 Of 1984, the provisions of the Transfer of Liability in International Sale were codified، and its provisions were quoted from the rules of the Encoterms of 1980، and in respect of the Vienna Convention on the International Sale of Goods they differed in determining the moment of transfer of liability as the contract of sale was in conjunction with the "carriage of goods." The liability shall be transferred by the delivery of the goods to the first carrier provided that it is independent. "In the latter case، it requires the transfer of liability from the buyer or the breach of the latter by the receipt of the goods. The Convention also deals with the status of determining which party is liable for loss in cases where the goods are sold during their transfer.